2012
DOI: 10.17221/6306-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitosan-oligosaccharide on diarrhoea in Hanwoo calves

Abstract: ABSTRACT:The therapeutic effect of Chitosan-oligosaccharide (COS) on calf diarrhoea was investigated in Korean native (Hanwoo) calves (n = 86). The calves were divided into two groups; the untreated/control (n = 40) having routine diet only and the treated group (n = 46) receiving COS (50 ml/day) in addition to the routine diet for five days. Blood samples from each animal were collected before and after five days treatment and were subjected to complete blood count (CBC), chemistry screening (CS) and plasma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The lower TP concentration might be also associated with the decrease in other proteins (e.g., globulins). A lower α-globulin accompanied by high albumin concentrations in calves transported for 18 h might be related to water loss (Alam et al, 2012), suggesting that these calves might have experienced dehydration at this time point. A great increase in sodium concentrations was particularly visible from 4 h (141.3 mmol/L) to 48 h (162.5 mmol/L) posttransport.…”
Section: Effects Of Experimental Treatments On Variables Until Wk 5 Posttransportmentioning
confidence: 99%
“…The lower TP concentration might be also associated with the decrease in other proteins (e.g., globulins). A lower α-globulin accompanied by high albumin concentrations in calves transported for 18 h might be related to water loss (Alam et al, 2012), suggesting that these calves might have experienced dehydration at this time point. A great increase in sodium concentrations was particularly visible from 4 h (141.3 mmol/L) to 48 h (162.5 mmol/L) posttransport.…”
Section: Effects Of Experimental Treatments On Variables Until Wk 5 Posttransportmentioning
confidence: 99%
“…In a previous study, KIM et al (2001) reported that administration of 500, 1000, and 2000 (mg/kg/day) doses of COS did not affect the hematological parameters (WBC, RBC, HGB, HCT, MCV, PLT, MPV, Lym, Mid and Gran) in rats. Similarly, COS (50 mL/day, during 5 days) treatment did not lead to significant differences in the values of PLT, MCV, MCH and MCHC in Hanwoo calves (ALAM et al, 2012). These different results may have been obtained due to the different doses or animal species.…”
Section: Discussionmentioning
confidence: 73%
“…In the same study, it has been reported that both excreted oocysts and developmental stage parasites were reduced and chitosan had anti-inflammatory activity (Abdel-Latif et al, 2016). In a study, oral chitosan oligosaccharide administering in the treatment of diarrheal calves has been reported to be very successful (Alam et al, 2012). In addition, chitosan has been used to create excipients in a microparticle system and it has been reported that it might play a role as a physical barrier against Cryptosporidium parvum (Blanco-García et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan and chitosan oligosaccharide (COS) have important uses in the medical field, such as controlled drug release, artificial blood vessels, antidiabetic, antibacterial, antifungal and hemostatic effect (Baldrick, 2010;Xia et al, 2011;Muanprasat and Chatsudthipong, 2017). In a study on the treatment of calves with diarrhea, oral chitosan oligosaccharide administration has been reported to be successful in treatment (Alam et al, 2012). In studies conducted, chitosan has been reported to inhibit the in vitro development of C. parvum (Luzardo Álvarez et al, 2012;Adjou et al, 2014;Mammeri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%